Patient-related risk factors associated with less favourable outcomes following hip arthroscopy: a scoping review. (July 2020) - Kuroda, Yuichi; Saito, Masayoshi; Çınar, Ece Nur; Norrish, Alan; Khanduja, Vikas
Abstract : Aims: This paper aims to review the evidence for patient-related factors associated with less favourable outcomes following hip arthroscopy. Methods: Literature reporting on preoperative patient-related risk factors and outcomes following hip arthroscopy were systematically identified from a computer-assisted literature search of Pubmed (Medline), Embase, and Cochrane Library using Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines and a scoping review. Results: Assessment of these texts yielded 101 final articles involving 90, 315 hips for qualitative analysis. The most frequently reported risk factor related to a less favourable outcome after hip arthroscopy was older age and preoperative osteoarthritis of the hip. This was followed by female sex and patients who have low preoperative clinical scores, severe hip dysplasia, altered hip morphology (excess acetabular retroversion or excess femoral anteversion or retroversion), or a large cam deformity. Patients receiving workers' compensation or with rheumatoid arthritis were also more likely to have a less favourable outcome after hip arthroscopy. There is evidence that obesity, smoking, drinking alcohol, and a history of mental illness may be associated with marginally less favourable outcomes after hip arthroscopy. Athletes (except for ice hockey players) enjoy a more rapid recovery after hip arthroscopy than non-athletes. Finally, patients who have a favourable response to local anaesthetic are more likely to have a favourable outcome after hip arthroscopy. Conclusion: Certain patient-related risk factors are associated with less favourable outcomes following hip arthroscopy. Understanding these risk factors will allow the appropriate surgical indications for hip arthroscopy to be further refined and help patients to comprehend their individual risk profile. Cite this article: Bone Joint J 2020;102-B(7):822–831.